Fenofibrate-promoted hepatomegaly and liver regeneration are PPARα-dependent and partially related to the YAP pathway - Shicheng Fan; Yue Gao; Pengfei Zhao; Guomin Xie; Yanying Zhou; Xiao Yang; Xuan Li; Shuaishuai Zhang; Frank J. Gonzalez; Aijuan Qu; Min Huang; Huichang Bi (Elsevier, 2024)
Fenofibrate, a peroxisome proliferator-activated receptor α (PPARα) agonist, is widely prescribed for hyperlipidemia management. Recent studies also showed that it has therapeutic potential in various liver diseases. However, its effects on hepatomegaly and liver regeneration and the involved mechanisms remain unclear. Here, the study showed that fenofibrate significantly promoted liver enlargement and regeneration post-partial hepatectomy in mice, which was dependent on hepatocyte-expressed PPARα. Yes-associated protein (YAP) is pivotal in manipulating liver growth and regeneration. We further identified that fenofibrate activated YAP signaling by suppressing its K48-linked ubiquitination, promoting its K63-linked ubiquitination, and enhancing the interaction and transcriptional activity of the YAP-TEAD complex. Pharmacological inhibition of YAP-TEAD interaction using verteporfin or suppression of YAP using AAV Yap shRNA in mice significantly attenuated fenofibrate-induced hepatomegaly. Other factors, such as MYC, KRT23, RAS, and RHOA, might also participate in fenofibrate-promoted hepatomegaly and liver regeneration. These studies demonstrate that fenofibrate-promoted liver enlargement and regeneration are PPARα-dependent and partially through activating the YAP signaling, with clinical implications of fenofibrate as a novel therapeutic agent for promoting liver regeneration.